INTEGRATED AND DIFFERENTIATED TEACHING TEENAGERS WITH MENTAL RETARDATION AND THEIR PERSONAL DEVELOPMENT - I. A. Koneva (Вестник Мининского университета, 2017)
This article discusses the relevance of the implementation of inclusive forms of education of children and teenagers with the limited possibilities of health in Russia. The analysis of comparative psychological studies on the problem of personal development of adolescents with mental retardation, studying and living in different pedagogical conditions of educational integration and differentiation. The analysis shows mostly negative for the mental development of children the experience of implementing the integrated model in modern Russian conditions. Emphasises the importance of the personality characteristics of children with disabilities health and harmonious personal development of children and adolescents with disabilities, particularly with mental retardation in inclusive models of training and education, the relevance of the organization of correctional-developing work aimed at optimizing the personal development of children.